2006
DOI: 10.1002/arp.276
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional and three‐dimensional resistivity imaging in archaeological site investigation

Abstract: In this work, the application and the effectiveness of two-and three-dimensional non-linear inversion algorithms in processing and interpretation of electrical resistivity tomography (ERT) data collected from archaeological areas are investigated in the framework of a new field technique for gathering three-dimensional pole^pole tomographic data in a relatively small amount of time using standard archaeological prospection equipment. The inversion routine, for both the two-dimensional and the three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 35 publications
2
91
0
2
Order By: Relevance
“…Given the three-dimensional nature of the problem studied, we decided to acquire dense survey lines, to allow full 3D processing of the data (Papadopoulos et al, 2006). We measured a dense grid of parallel -and a few perpendicular -2D ERT lines.…”
Section: Ert: Data Acquisition Processing and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the three-dimensional nature of the problem studied, we decided to acquire dense survey lines, to allow full 3D processing of the data (Papadopoulos et al, 2006). We measured a dense grid of parallel -and a few perpendicular -2D ERT lines.…”
Section: Ert: Data Acquisition Processing and Resultsmentioning
confidence: 99%
“…Note that this approach is much more time-consuming compared to the 2D one and can be applied only in areas where several parallel ERT lines (i.e., > 4) are collected. Although the data acquisition is a set of 2D measuring sections, it has been shown that in this case fully 3D imaging is possible when inversion is performed by fully 3D algorithms (Papadopoulos et al, 2006;. Also, the data have to be collected along dense parallel traverses, which ideally should be spaced at intervals equal to the spacing of the electrodes along the traverse.…”
Section: XLVII No 3 -1359mentioning
confidence: 99%
“…This inversion technique employed finite elements using 2256 cells for the calculation of the apparent resistivity data (forward problem) and the blocky (robust) inversion (Claerbout & Muir, 1973). This gives reasonably accurate images of three-dimensional structures, bigger than 5x5x10 m, enabling the 3D imaging of the subsurface using costeffective 2D electric tomography techniques (Dahlin & Loke, 1997;Papadopoulos et al, 2006;Tsokas et al, 2008;Chang et al, 2011). The depth slices (Fig.…”
Section: Electrical Tomography Gridmentioning
confidence: 95%
“…This data set can be inverted for the true subsurface resistivity by using 2D or 3D inversion algorithms and the resulting estimated models can be interpreted accordingly (Papadopoulos et al 2006). Electrical resistivity tomography is a method adapted to the recognition and study of 2D structures perpendicular to the profile and to the identification of the various geological layers, including the surface cover, but is more expensive and time consuming than the electromagnetic survey.…”
Section: Electrical Resistivity Tomography (Ert)mentioning
confidence: 99%